Brilliant Brainiac Home Tutoring / Daniel Niezam Iskandar Tan … [et al.] - Iskandar Tan, Daniel Niezam; Hazrin Amri, Hidayatul Zurain; Muhammad Mulkan, Muhammad Husni Mulhim; Azman, Nur Adriana; Khairol Basri, Zinnirah (2021)
The name given for our company is Brilliant Brainiac Home Tutoring. The motto of our company is “Nurturing Young Minds”. The reason for the motto given is because our tutoring service are conducted by five science experts that will guide the young minds on how to ace well in examination as well as in life. This is because the teachers will give our best to help students to aim bigger and see clearer in their studies. The nature of our business is based on home tutoring services through online learning and also provides face-to-face tutoring within a specific area. Brilliant Brainiac Home Tutoring is a company in which the nature of business entity is partnership, where a legal business entity with five partners carries out the business with a view of making profits, share capital, profits and losses. Our tutoring service fee is around RM50 to RM70 per subject based on their level of education which are either primary students, secondary students or diploma students’ level. Brilliant Brainiac Home Tutoring is started to operate actively on the early year of 2018 at Jalan Medan Pusat Bandar, Seksyen 9, 43650, Selangor. We believed that the selected place is a very strategic location because Selangor was considered as the largest population in our country. We started our business right after we graduated with Diploma of Microbiology. Since this is our first experience in joining this field, we decided to open classes only for science streams students and also secondary students especially those who are struggling with PT3 and SPM examination. Our aim is not just to gain huge income every single month but, our biggest aim is to provide the best services towards all students out there who need help in studying and how to excel in examination. We provide the latest learning materials and formats especially in SPM examination. Despite this latest pandemic outbreak, our business is still growing well since we also provide an online learning teaching platform for them. Many students got interested in our teaching methods and decided to join our home tutoring.